From Lelia’s and Mrs. Albrecht’s Classrooms to Explore Who is the Native Speake - Li, Ke (Pacific International Journal, 2024)
Chang-Rae Lee’s novel, Native Speaker, narrates the story of the protagonist from a first-person perspective. Through observing his wife’s teaching instructions, Henry recalls his own experiences in an English classroom during his youth, where Mrs. Albrecht’s harsh methods and classmates' mockery eroded his confidence and even caused serious anxiety. The descriptions of Mrs. Albrecht’s classroom demonstrate the traumatic experience of marginalized immigrant children. Henry Park, a 1.5 generation of Korean-American immigrant, imitates a polished English accent to be assimilated into American mainstream society. However, his excessive carefulness to details prevents him from becoming a true “native speaker”, and from the inner world, he is simultaneously influenced by both Korean culture and American culture. Henry’s “dual identity” leads him to be employed by an immigration intelligence agency, and he is assigned to infiltrate the camp of Korean-American politician--John Kwang, a candidate for the city mayor. In his interactions with John Kwang, Henry is confronted with an identity crisis as an Asian-American. Consequently, the issues of language, identity, and the political rights of minority ethnic groups arise.